Structural Modeling of the Tendency Toward Aggression Based on Social Acceptance with the Mediation of Childhood Abuse Experience in Neglected and Orphaned Children - Azadmanesh, Saeideh; Khajevand Khoshli, Afsaneh; Azizi, Leila (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: The main objective of this study is to model the structural relationships of the tendency toward aggression based on social acceptance with the mediation of childhood abuse experience. Methods and Materials: The research method is correlational, based on structural equation modeling. The statistical population of this study includes 309 neglected and orphaned children. Considering the number of latent variables in this study, a sample of 250 individuals was selected. The sampling method is stratified sampling. The data collection tools include the Aggression Questionnaire by Nielson et al. (2000), the Social Acceptance Questionnaire by Crowne and Marlowe (1960), and the Child Abuse Questionnaire (Self-report Scale) by Nourbakhsh (2012). Structural equation modeling was used for data analysis, and SPSS and LISREL software were employed for data processing. Findings: The results from the research data indicate a relationship between social acceptance and childhood abuse experience and the tendency toward aggression in neglected and orphaned children. There is also a relationship between childhood abuse experience and the tendency toward aggression in neglected and orphaned children. Furthermore, a relationship exists between social acceptance and the tendency toward aggression through the mediation of childhood abuse experience in neglected and orphaned children. Conclusion: Enhancing social acceptance may reduce aggressive behaviors and improve mental health outcomes, emphasizing the need for supportive interventions and targeted programs to address the unique challenges faced by these children.